Integrating competency-based, interprofessional teamwork education for students: guiding principles to support current needs and future directions - Kimberly N. Williams; Elizabeth H. Lazzara; Jessica Hernandez; David Klocko; Neethu Chandran; Shannon L. Paquette; Richard Preble; Mozhdeh Sadighi; Bau Tran; Molly Kilcullen; Robert Rege; Gary Reed; et al. (Frontiers in Medicine)
Interprofessional teamwork is vital to effective patient care, and targeting healthcare learners earlier in their education can lead to greater improvement in confidence and competence in teamwork skills. Despite this, institutions have continued struggling to integrate competency-based interprofessional teamwork curriculum in undergraduate health care professions’ education. The current article provides guidance related to design, implementation, and assessment for institutions seeking to implement competency-based teamwork education and training strategies for healthcare students. Guiding principles and strategies for curricular design focus on conducting thorough interprofessional needs analyses and building transportable, evidence-based competencies that apply across professions. For implementation, key principles center on strategies to ensure adequate professional representation and faculty development. Assessment considerations focus on building infrastructure for evaluation that spans professional schools. These strategies aim to create a robust, effective, and sustainable IPE curriculum that enhances collaboration and teamwork among future healthcare professionals. By addressing the key areas of design, implementation, and assessment, this article offers comprehensive guidelines for advancing interprofessional education. We believe incorporating the key guiding principles and strategies from this paper will enable institutions to integrate teamwork education and training more effectively into undergraduate healthcare training, which will facilitate institutions’ ability to ensure learners are “team ready” as they transition into the workforce after graduation.